Clinical manifestations, diagnostic criteria, and treatment outcomes of minocycline-associated DRESS syndrome: a comprehensive exploration of published cases - Pan, Yan; Wu, Qiquan (Frontiers in Pharmacology, 2025)
IntroductionMinocycline can induce a rare but serious adverse drug reaction known as drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome. We explored the clinical features of minocycline-associated DRESS to aid in early diagnosis and risk mitigation.MethodsA comprehensive exploration of published cases from the start of electronic databases (PubMed, Embase, Web of Science, CNKI, Wanfang Data) to December 1, 2024. Cases were screened using RegiSCAR criteria.ResultsA total of 3,928 citations were identified through database searches, and after screening, 39 case reports (comprising 57 patients) were included. Fifty-seven patients (mean age 37.1 years) exhibited median DRESS onset at 17.5 days. Respiratory symptoms (87.7%, n = 50) dominated, including non-productive cough, dyspnea, pharyngitis, and wheezing. Fever occurred in 45 (78.9%) patients. Median eosinophilia peaked at 4.09 × 109/L. Symptom improvement median time was 10.5 days. Overall, forty-five patients (93.8% of 48 with outcome data) recovered post-minocycline discontinuation. Four deaths occurred (hepatic failure, refractory hypotension, unknown causes).ConclusionMinocycline-associated DRESS syndrome is characterized by diverse clinical manifestations, including prominent respiratory symptoms. Timely drug cessation, corticosteroid therapy, and vigilant monitoring are critical to optimize outcomes. These findings underscore the need for enhanced pharmacovigilance in high-risk populations.